Use the geometric series to compute the Taylor series for
. . . . .\(\displaystyle f(x)\, =\, \dfrac{1}{2\, -\, x}\)
Where does this series converge? Hint:
. . . . .\(\displaystyle \dfrac{1}{2\, -\, x}\, =\, \dfrac{1}{2}\, \dfrac{1}{1\, -\, \frac{x}{2}}\)
I know the following series converges while |x| < 1:
. . . . .\(\displaystyle \displaystyle \dfrac{1}{1\, -\, x}\, =\, \sum_{k=0}^{\infty}\, x^k\)
Which must mean that
. . . . .\(\displaystyle \displaystyle \dfrac{1}{2}\, \dfrac{1}{1\, -\, \frac{x}{2}}\, =\, \dfrac{1}{2}\, \sum_{k=0}^{\infty}\, \left(\dfrac{x}{2}\right)^k\)
converges while
. . . . .\(\displaystyle \displaystyle \bigg|\dfrac{x}{2}\bigg|\, <\, 1, \Longleftrightarrow\, |x|\, <\, 2\)
What if I had approached this problem in a different way?
. . . . .\(\displaystyle \displaystyle \dfrac{1}{2\, -\, x}\, =\, \dfrac{1}{1\, -\, (x\, -\, 1)}\)
Which means that
. . . . .\(\displaystyle \displaystyle \dfrac{1}{1\, -\, (x\, -\, 1)}\, =\, \sum_{k=0}^{\infty}\, (x\, -\, 1)^k\)
converges while
. . . . .\(\displaystyle \displaystyle |x\, -\, 1|\, <\, 1\, \Longleftrightarrow\, 0\, <\, x\, <\, 2\)
What am I missing here? Both answers can't be correct. Is neither correct?
. . . . .\(\displaystyle f(x)\, =\, \dfrac{1}{2\, -\, x}\)
Where does this series converge? Hint:
. . . . .\(\displaystyle \dfrac{1}{2\, -\, x}\, =\, \dfrac{1}{2}\, \dfrac{1}{1\, -\, \frac{x}{2}}\)
I know the following series converges while |x| < 1:
. . . . .\(\displaystyle \displaystyle \dfrac{1}{1\, -\, x}\, =\, \sum_{k=0}^{\infty}\, x^k\)
Which must mean that
. . . . .\(\displaystyle \displaystyle \dfrac{1}{2}\, \dfrac{1}{1\, -\, \frac{x}{2}}\, =\, \dfrac{1}{2}\, \sum_{k=0}^{\infty}\, \left(\dfrac{x}{2}\right)^k\)
converges while
. . . . .\(\displaystyle \displaystyle \bigg|\dfrac{x}{2}\bigg|\, <\, 1, \Longleftrightarrow\, |x|\, <\, 2\)
What if I had approached this problem in a different way?
. . . . .\(\displaystyle \displaystyle \dfrac{1}{2\, -\, x}\, =\, \dfrac{1}{1\, -\, (x\, -\, 1)}\)
Which means that
. . . . .\(\displaystyle \displaystyle \dfrac{1}{1\, -\, (x\, -\, 1)}\, =\, \sum_{k=0}^{\infty}\, (x\, -\, 1)^k\)
converges while
. . . . .\(\displaystyle \displaystyle |x\, -\, 1|\, <\, 1\, \Longleftrightarrow\, 0\, <\, x\, <\, 2\)
What am I missing here? Both answers can't be correct. Is neither correct?
Attachments
Last edited by a moderator: